Dealing with populists in government: a framework for analysis. Issue 2 (23rd February 2016) - Kaltwasser, Cristóbal Rovira; Taggart, Paul
Abstract : There is growing research on populist actors and their impact on the democratic system, but little has been written on how to deal with populist actors in government. To respond to this question, in this article we develop a theoretical framework that distinguishes three levels of analysis. First, we identify the set of domestic and external actors that can try to cope with the coming into power of populist forces. Second, we offer an overview of the different strategies that can be employed to react against populist actors in government. Third, we argue that it is important to consider the timing of the reactions. In addition, we also present a brief summary of the articles that are part of this special issue.